Retrieval comparison of EndNote to search MEDLINE (Ovid and PubMed) versus searching them directly. - Gall C; Brahmi FA (Medical Reference Services Quarterly)
Using EndNote version 7.0, the authors tested the search capabilities of the EndNote search engine for retrieving citations from MEDLINE for importation into EndNote, a citation management software package. Ovid MEDLINE and PubMed were selected for the comparison. Several searches were performed on Ovid MEDLINE and PubMed using EndNote as the search engine, and the same searches were run on both Ovid and PubMed directly. Findings indicate that it is preferable to search MEDLINE directly rather than using EndNote. The publishers of EndNote do warn its users about the limitations of their product as a search engine when searching external databases. In this article, the limitations of EndNote as a search engine for searching MEDLINE were explored as related to MeSH, non-MeSH, citation verification, and author searching.